LEARNING A LANGUAGE IS LEARNING A CULTURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides information about the symbiotic relationships between language and culture.Learning a new language goes far beyond acquiring the ability to communicate. It’s an immersive experience, one that ties together not just words and grammar, but traditions, values, and customs that define a culture. Language is the vehicle through which a community expresses its worldview, and understanding a language means tapping into the heart of the culture it represents. This article delves into the concept that "learning a language is learning a culture," exploring how language and culture are intertwined in various global contexts.